Taxonomic revision of Serica MacLeay, 1819 (sensu lato) from China and adjacent areas (Coleoptera: Scarabaeidae: Melolonthinae: Sericini), with updates on Nipponoserica Nomura, 1972 - Ahrens, Dirk; Fabrizi, Silvia; Bai, Ming; Liu, Wangang (Zootaxa, 2022)
In this paper we revised the species of Serica McLeay, 1819 (sensu lato) occurring in China an adjacent areas, and provide an update on the genus Nipponoserica Nomura, 1972. The revision resulted in one new combination: Serica adspersa (Frey, 1972), new combination. Thirty-nine new species are described: Nipponoserica daqiao Ahrens, Fabrizi & Liu, new species, Serica allolongipes Ahrens, Fabrizi & Liu, new species, S. allotengchongana Ahrens, Fabrizi & Liu, new species, S. baishuitaiensis Ahrens, Fabrizi & Liu, new species, S. baoshan Ahrens, Fabrizi & Liu, new species, S. daqiaoana Ahrens, Fabrizi & Liu, new species, S. dissimillima Ahrens, Fabrizi & Liu, new species, S. emaw Ahrens, Fabrizi & Liu, new species, S. gaoligong Ahrens, Fabrizi & Liu, new species, S. guangnanensis Ahrens, Fabrizi & Liu, new species, S. hailuogou Ahrens, Fabrizi & Liu, new species, S. huangbaiyuanensis Ahrens, Fabrizi & Liu, new species, S. huangjing Ahrens, Fabrizi & Liu, new species, S. jani Ahrens, Fabrizi & Liu, new species, S. jaroslavi Ahrens, Fabrizi & Liu, new species, S. jiankouensis Ahrens, Fabrizi & Liu, new species, S. jirii Ahrens, Fabrizi & Liu, new species, S. kuankuoshuiensis Ahrens, Fabrizi & Liu, new species, S. limbourgi Ahrens, Fabrizi & Liu, new species, S. longipes longipes Ahrens, Fabrizi & Liu, new species, S. longwang Ahrens, Fabrizi & Liu, new species, S. mengsongana Ahrens, Fabrizi & Liu, new species, S. nanhua Ahrens, Fabrizi & Liu, new species, S. pangwa Ahrens, Fabrizi & Liu, new species, S. paralongipes Ahrens, Fabrizi & Liu, new species, S. paralupina Ahrens, Fabrizi & Liu, new species, S. pseudogracilipes Ahrens, Fabrizi & Liu, new species, S. shengtangshan Ahrens, Fabrizi & Liu, new species, S. shiduensis Ahrens, Fabrizi & Liu, new species, S. smetanai Ahrens, Fabrizi & Liu, new species, S. taishun Ahrens, Fabrizi & Liu, new species, S. tengchongana Ahrens, Fabrizi & Liu, new species, S. tianmushan Ahrens, Fabrizi & Liu, new species, S. tianpingshanensis Ahrens, Fabrizi & Liu, new species, S. yini Ahrens, Fabrizi & Liu, new species, S. yuheba Ahrens, Fabrizi & Liu, new species, S. zhenba Ahrens, Fabrizi & Liu, new species, S. ziqingi Ahrens, Fabrizi & Liu, new species. A key to species groups and species within groups is given, habitus and male genitalia of the revised species are illustrated. The distribution of the species revised herein is shown on maps. New distributional data are given for sixteen species.